POLA STRUKTUR REGIONAL JAWA BARAT - Helmi, Faisal; Haryanto, Iyan (Bulletin of Scientific Contribution, 2008)
Regional structure of West Java influenced by interaction of subduction between India-Australia plate with Eurasia plate. Effect of this subduction, in West Java expand some fault structure which devide to 4 faults, that is north-south faults, northwest-southeast faults, and northeast-southwest faults.Fault of North-South which devide into Sunda Pattern, is representing oldest fault and forming of Paleogen Basin in West Java. Stress system of Sunda Pattern is influenced by transtensional tectonic and as a whole form structure pattern of negative structure flower.Change of tectonics in West Java take place at Plio-Plistosen period. At that moment system of stress influenced by tectonic compression yielding fold structure of wast-east thrust-fault (Java Pattern). At same tectonic period, formed a number of northwest-southwest strike-slip fault (Sumatera Pattern) and northeast-southwest strike-slip fault (Meratus Pattern).